Stories of change in nutrition from Africa and Asia: an introduction to a special series in Food Security - Gillespie, Stuart (Food Secur, 2021)
Malnutrition in all its forms continues to be a massive global challenge, and the past decade has seen a growing political attention to addressing malnutrition in different contexts. What has been largely missing so far, and is in growing demand from countries, is tangible, practical and rigorous insights and lessons (from other countries or contexts) on how to translate this burgeoning political momentum into effective policies and programme implementation strategies – and ultimately impact on the ground. This new climate of learning from experience and evidence led to the launch in 2015 of the Stories of Change initiative. This series presents a second wave of studies from six countries (Tanzania, Rwanda, Vietnam, Ghana, Burkina Faso, Nigeria,) and three Indian states (Chhattisgarh, Gujarat, Tamil Nadu). These provide clear evidence combined with compelling narratives on what drives success in addressing all forms of malnutrition – evidence that is necessary for turning global momentum into actual results on the ground. This introductory Opinion is published with the first set of papers. It will be followed by a thorough synthesis of papers as a conclusion of the Series. We hope that the lessons embedded in these Stories of Change will inform and inspire the deliberations and outcomes of the UN Food Systems Summit and the second Nutrition for Growth Summit to be held this year, and the actions of those in the global food and nutrition system working for positive change.